Analisis Terhadap Putusan Peninjauan Kembali Mahkamah Agung Republik Indonesia (Studi Putusan PK MA Republik Indonesia No. 97 PK/PID.SUS/2012) - Marsudi Utoyo (Universitas Bandar Lampung (UBL), 2015)
Corruption in Indonesia is a nation that has faced problems since ancient times, so that the special court of corruption is expected to help resolve a number of criminal cases of corruption in order to restore the state of wealth that has been lost. The research problem is how the procedure of judicial review of the Supreme Court of the Republic of Indonesia on the Supreme Court Decision No. 97 PK / PID.SUS / 2012. Ie normative juridical approach method, data analysis is qualitative. The results showed the effort of law. Request for reconsideration on the basis of a) if there are new circumstances that give rise to strong suspicion, that if the circumstances had been known at the time the trial is still ongoing, the outcome would be acquittal or a verdict free from any lawsuits or claims prosecutor unacceptable or against The court applied the criminal provisions of the lighter, b) if there is a verdict in the various statements that something has been proven, but the thing or situation as the basis and reasons stated verdict has proved that, it has been at odds with one another and c) if the verdict it clearly shows a missjudge or a real mistake.